The impact of macroeconomics variables on price level in Malaysia / Nur Syafiqah Nazurah Tajul Amir Hashim - Tajul Amir Hashim, Nur Syafiqah Nazurah (2022)
Both inflation and deflation can give good or bad impact depends on the country. Thus, the objectives of this study are to find the relationship between each macroeconomics variables and price level in Malaysia and to investigate the impact of macroeconomics variables on price level in Malaysia for the period of 1988 to 2018. The independent variables used include money supply, unemployment rate, import of goods and services and deficits fiscal balance. Dynamic Ordinary Least Square (DOLS) method was used to analyze the data collected from World Bank Data and Bank Negara Malaysia (BNM) in order to understand the impact of macroeconomics variables on price level in Malaysia. The results revealed that all of the independent variables have a positive but insignificant relationship with price level in Malaysia. The research findings will assists the Malaysia’s policy makers with some information to help them to make policies. This study also will enrich the knowledge on macroeconomics factors that affect price level.